Efforts to Reduce Stress by Interpreting Life from Religious Rituals Lived by an Individual - Rohmadani, Zahro Varisna; Khoiryasdien, Andhita Dyorita (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
Everyone has experienced stres. Stress is felt when a person is unable to cope with an unpleasant situation. Some of the things that are the origin of stres, namely, the environment that comes from the nature of the environment itself, the demands of the family, and technological developments that make a person must always be updated, then the self which consists of psychological needs and the process of self-internalization, and the last one is self. thoughts related to the assessment and adjustment of the individual to the environment. Stress can be overcome by someone, one of them is by performing religious rituals. Religious rituals performed by a person can help them to give meaning to life. The purpose of this study is to see the effect of the meaning of life with religious rituals to reduce stres. This study uses 3 variables with the data collection method using a scale. The sample used in this study were 187 adolescents. The results obtained indicate that the meaning of life through religious rituals can reduce stres with score 14,3%.Setiap individu pernah mengalami stres. Stres dirasakan ketika seseorang tidak mampu mengatasi situasi yang tidak menyenangkan. Beberapa hal yang menjadi sumber asal dari stres yaitu, lingkungan yang bersumber dari sifat lingkungan itu sendiri, tuntutan keluarga, serta perkembangan teknologi yang membuat seseorang harus selalu update, serta diri sendiri yang terdiri dari kebutuhan psikologis dan proses internalisasi diri,  pikiran yang berkaitan dengan penilaian dan penyesuaian individu terhadap lingkungan. Stres dapat diatasi oleh seseorang salah satunya dengan ritual agama yang dilakukan. Ritual agama yang dilakukan oleh seseorang ini bisa membantu mereka untuk memberikan pemaknaan hidup. Tujuan penelitian ini yaitu untuk melihat pengaruh pemaknaan hidup dengan ritual agama untuk menurunkan stres. Penelitian ini menggunakan 3 variabel dengan pengumpulan data menggunakan skala. Sampel di penelitian ini adalah 187 remaja. Hasil yang didapatkan menunjukkan bahwa pemaknaan hidup melalui ritual agama dapat menurunkan stres dengan pengaruh variabel kebermaknaan hidup dan ritual agama terhadap stres sebesar 14,3% .